2012
DOI: 10.1161/strokeaha.112.657007
|View full text |Cite
|
Sign up to set email alerts
|

IL1B and VWF Variants Are Associated With Fibrinolytic Early Recanalization in Patients With Ischemic Stroke

Abstract: Background and Purpose-There is a great interindividual variability among patients with acute ischemic stroke regarding the response to intravenous tissue-type plasminogen activator treatment. The aim of this study was to identify genetic variants associated with recanalization, and thus treatment efficacy, after tissue-type plasminogen activator administration. Methods-A total of 140 single nucleotide polymorphisms from 97 candidate genes were successfully genotyped by SNPlex in 2 cohorts, accounting for 497 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…IL-6, another inflammatory cytokine secreted by vascular endothelial cells and macrophages, is also highly expressed in the serum of patients with acute cerebral infarction and is positively correlated to cerebral infarction size and degree of neurologic impairment (Xu et al, 2005;Choi et al, 2014). IL-1β is a major inflammatory-promoting cytokine, and it has been demonstrated that serum levels of IL-1β in patients with cerebral infarction are significantly increased, which is possibly associated with the development of cerebral infarction (Fernández-Cadenas et al, 2012). In the current study, the analysis of serum levels of inflammatory cytokines including IL-6, TNF-α and IL-1β in patients with cerebral infarction revealed higher than normal expression levels of these cytokines, which is consistent with previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-6, another inflammatory cytokine secreted by vascular endothelial cells and macrophages, is also highly expressed in the serum of patients with acute cerebral infarction and is positively correlated to cerebral infarction size and degree of neurologic impairment (Xu et al, 2005;Choi et al, 2014). IL-1β is a major inflammatory-promoting cytokine, and it has been demonstrated that serum levels of IL-1β in patients with cerebral infarction are significantly increased, which is possibly associated with the development of cerebral infarction (Fernández-Cadenas et al, 2012). In the current study, the analysis of serum levels of inflammatory cytokines including IL-6, TNF-α and IL-1β in patients with cerebral infarction revealed higher than normal expression levels of these cytokines, which is consistent with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Tanshinone and salvianolic acid can reduce blood viscosity, increase blood flow and erythrocyte deformation, inhibit thrombosis, scavenge free radicals, and improve microcirculation. Carthamin can dilate blood vessels, reduce platelet aggregation, and inhibit thrombosis (Fernández-Cadenas et al, 2012). Additionally, it has been reported that Danhong injection inhibits the expression of inflammatory cytokines and the resultant inflammatory cascade and reduces damage to organs and cells (Wang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The IST (International Stroke Trial)-3 randomized the largest cohort of patients (3035) to IV tPA versus placebo and showed that despite early hazards from an increased risk of ICH, thrombolysis within 6 hours improved functional outcomes even in patients aged >80 years. 78 Although some studies have suggested that genetic polymorphisms, 79,80 race, and sex may influence the efficacy of tPA, 81,82 only certain comorbidities such as hypertension and hyperglycemia have been found to significantly and negatively impact thrombolytic response in AIS patients.…”
Section: Intravenous Thrombolysismentioning
confidence: 99%
“…33,34 Large efforts on studying genetic impact on early treatment effects of thrombolysis are underway. 40 Longer term prognosis on neurological/physical deficit can be grouped into neurological outcomes, stroke recurrence, and mortality. Alterations in the BDNF gene are often studied in stroke recovery.…”
Section: Neurological/physical Deficitmentioning
confidence: 99%
“…A study of 140 single nucleotide polymorphisms in ischemic stroke patients treated with tissue-type plasminogen activator reported that variants in the IL1B and vWF genes were associated with early recanalization and suggested a relation to activity of coagulation factors. 40 In a microarray study, patients with hemorrhagic transformation after tissue-type plasminogen activator treatment had altered expression of genes related to apoptosis and neutrophil regulation pathways. 68 The genetic impact on metabolism and response to anticoagulation therapy would have important clinical consequences for stroke recovery.…”
Section: September 2016mentioning
confidence: 99%